2018
DOI: 10.1371/journal.pone.0191937
|View full text |Cite
|
Sign up to set email alerts
|

Short-term repeated HRV-16 exposure results in an attenuated immune response in vivo in humans

Abstract: IntroductionNaturally, development of adaptive immunity following HRV infection affects the immune response. However, it is currently unclear whether or not HRV re-exposure within a short time frame leads to an altered innate immune response. The “experimental cold model” is used to investigate the pathogenesis of HRV infection and allows us to investigate the effects of repeated exposure on both local and systemic innate immunity.Methods40 healthy male and female (1:1) subjects were nasally inoculated with HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…These studies suggest viral infection induced alteration of the immunologic homeostasis of the sinonasal mucosa, which could promote secondary bacterial infection. Interestingly, Koch et al also found repeated inoculation with RV 1 week after initial exposure had attenuated cytokine response 370 . This is consistent with anti‐inflammatory and immunosuppressive functions for IL‐10 seen in overexpression experiments by Stanic et al and could provide a mechanism for ABRS following RV infection 372 …”
Section: Acute Rhinosinusitis (Ars)supporting
confidence: 59%
See 2 more Smart Citations
“…These studies suggest viral infection induced alteration of the immunologic homeostasis of the sinonasal mucosa, which could promote secondary bacterial infection. Interestingly, Koch et al also found repeated inoculation with RV 1 week after initial exposure had attenuated cytokine response 370 . This is consistent with anti‐inflammatory and immunosuppressive functions for IL‐10 seen in overexpression experiments by Stanic et al and could provide a mechanism for ABRS following RV infection 372 …”
Section: Acute Rhinosinusitis (Ars)supporting
confidence: 59%
“…Both studies found early increases in IL‐10 in controls exposed to RV. Koch et al also showed increases in IL‐6 and interferon gamma‐induced protein‐10 370 . These studies suggest viral infection induced alteration of the immunologic homeostasis of the sinonasal mucosa, which could promote secondary bacterial infection.…”
Section: Acute Rhinosinusitis (Ars)mentioning
confidence: 91%
See 1 more Smart Citation
“…They are the major cause of the "common cold" via infection of the upper respiratory tract and are estimated to be responsible for up to half of all human infections [17]. Despite this impressive pathogenicity, in a study of short-term repeated HRV exposure, most (82%), but not all, human subjects infected with high titers of HRV caught colds, even when exposed directly through the upper respiratory tract [18]. Symptoms from infection tend to be mild and HRVs are eventually cleared from the body, though it has proven incredibly challenging, if not impossible, to generate effective vaccines [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Local immune responses to RV16 infection include the release of interferons and other pro-inflammatory mediators such as CXCL-10 and CXCL-8 leading to infiltration of inflammatory cells. Besides local responses, there are systemic responses including increased levels of T-helper and T-regulatory cell type cytokines [ 14 ] as well as an increase in plasma levels of CXCL-10 [ 15 , 16 ] and production of antibodies. RV16 challenge studies have also been employed to test the efficacy of various therapeutics [ 17 ].…”
Section: Introductionmentioning
confidence: 99%